Presence of antibodies against some pathogens of zoonotic interest in four pig farms of Cundinamarca, Colombia - Pulido-Villamarín, Adriana (2019)
The aim of this study was to determine the presence of antibodies against pathogens of pigs that represent public health risk due to their zoonotic potential (Salmonella spp, Leptospira interrogans, Yersinia spp, Trichinella spp and Toxoplasma gondii) in porcine sera obtained in four semi-technified pig farms from Cundinamarca, Colombia. A total of 89 blood samples were collected and analyzed using the ELISA diagnostic kits Pigtype®- Salmonella Ab, Pigtype®-Yopscreen, Pigtype®-Toxoplasma Ab and Pigtype®-Trichinella (QuiaGen®) The detection of antibodies against Leptospira spp was carried out by the microagglutination lysis test (MAT). Antibodies against Salmonella spp was observed in 40% of the samples, while for Yersinia spp and Toxoplasma gondii was in 18 and 1.1% respectively. At least one of the 13 serovars of Leptospira interrogans was detected in all four farms and none of the samples was positive for Trichinella spp. It is concluded that the pigs in the study had contact at some point of their productive cycle with most of the zoonotic pathogens evaluated, which may represent a risk to public health and pig production.